Reformulasi Tafsir: Studi Pemikiran Gender Asghar Ali Engineer - Abdul Rasyid Ridho (UIN Mataram, 2020)
Asghar Ali Engineer is one of the figures who promotes and implements liberation theology. Liberation theology emphasizes praxis rather than metaphysical theoritization which includes abstract and ambiguous concepts. The praxis in question is of a liberal nature and involves dialectical attraction between